2018
DOI: 10.1590/1518-8345.2509.3036
|View full text |Cite
|
Sign up to set email alerts
|

Serious games as an educational strategy to control childhood obesity: a systematic literature review

Abstract: Objectives:to identify in the literature the efficacy of serious games to improve knowledge for and/or behavioral changes among overweight or obese children. Method:Systematic Literature Review. The Cochrane Systematic Reviews Handbook was used. The studies were collected from the following databases: Public Medline; Web Of Science; Science Direct; Latin American and Caribbean Health Sciences Literature; and the Health Game Research and Cumulative Index to Nursing & Allied Health Literature. The descriptors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
(43 reference statements)
0
24
0
10
Order By: Relevance
“…Existing systematic reviews of mHealth dietary interventions for children and adolescents were identified. These studies indicated that nutrition knowledge acquisition, nutrition-related behaviors, and nutrition-related health outcomes improve with mHealth interventions [7,9], and they highlighted the strengths of gamification as a strategy to implement for child nutrition mHealth apps [27,28]. An additional systematic search, conducted by the Foodbot Factory research and development team, focused on identifying other strategies demonstrated to engage children in learning or behavior change through mHealth nutrition apps [10,11,[29][30][31][32][33][34][35].…”
Section: Discoverymentioning
confidence: 99%
“…Existing systematic reviews of mHealth dietary interventions for children and adolescents were identified. These studies indicated that nutrition knowledge acquisition, nutrition-related behaviors, and nutrition-related health outcomes improve with mHealth interventions [7,9], and they highlighted the strengths of gamification as a strategy to implement for child nutrition mHealth apps [27,28]. An additional systematic search, conducted by the Foodbot Factory research and development team, focused on identifying other strategies demonstrated to engage children in learning or behavior change through mHealth nutrition apps [10,11,[29][30][31][32][33][34][35].…”
Section: Discoverymentioning
confidence: 99%
“…Serious games desenvolvidos pelo GPECCA mentais e promoção de melhores resultados de saúde. (22) Jogos proporcionam aprendizado baseado na experiência, que motiva o estudante, além de alguns possuírem pontuação que exibem o progresso e desempenho do aluno, sendo essa característica atrativa aos nativos digitais. (23) Outros benefícios importantes para a aprendizagem proporcionados pelos games incluem facilidade de acesso à informação desejada, fornecimento de respostas claras a difi culdades e problemas compatíveis com a realidade do aluno, síntese das melhores evidências científi cas e possiblidade de jogar via smartphone ou outros dispositivos móveis.…”
Section: Escolha E Preparação Do Método E Das Ferramentasunclassified
“…Such games can help a player master new moves (Nyberg & Meckbach, 2017) or fulfill some of the daily physical activity recommendations (Polechonski & Mynarski, 2018). • acquiring health knowledge about healthy eating habits in children, preventing childhood obesity (Dias et al, 2018), or supporting good habits among the sick or cancer patients (Thomas et al, 2019). SGs have also been used with people with asthma, though the increase in knowledge was not accompanied by increased motivation for treatment (Drummond & Monnier, 2017).…”
Section: Areas Of Use For Serious Gamesmentioning
confidence: 99%